Selective inhibition of responses to nerve growth factor and of microtubule-associated protein phosphorylation by activators of adenylate cyclase (The Rockefeller University Press, 1986)
To study the influence of cAMP on cellular responses to nerve growth factor (NGF) and to use elevation of intracellular cAMP to probe the NGF mechanism, cultured PC12 pheochromocytoma cells were exposed to forskolin and cholera toxin. As in other cell types, the latter agents greatly increased PC12 cell cAMP levels. Such treatment also brought about a reversible, dose-dependent suppression of NGF-promoted regeneration of neurites. In support of the role of cAMP in this effect, regeneration blockage by forskolin was potentiated by phosphodiesterase inhibitors. When tested on NGF-stimulated initiation of process outgrowth, cholera toxin and forskolin exerted a dual effect. As in previous studies, these drugs, when applied along with NGF, significantly enhanced the initial formation of short cytoplasmic extensions. However, after approximately 3 d of NGF exposure, at which time such extensions begin to acquire the morphological and ultrastructural features of neurites, these agents suppressed process outgrowth. That is, the neurites were fewer in number, significantly less branched, and much shorter than in control cultures. Such changes also occurred when these drugs were added to cultures that had been pretreated with NGF alone. Whereas forskolin and cholera toxin affect the formation and regeneration of neurites, these drugs did not interfere with the short-latency, transient changes in surface morphology that are triggered by NGF, nor did they inhibit transcription-dependent priming. In contrast, the rapidly occurring NGF- induced phosphorylation of tyrosine hydroxylase was suppressed. Moreover, forskolin and cholera toxin rapidly and selectively blocked the NGF-promoted phosphorylation of a set of microtubule-associated proteins known as chartins. Previous observations have suggested a causal relationship between NGF-induced chartin microtubule-associated protein phosphorylation and the formation and outgrowth of neurites. This is supported by the present data and provides a possible mechanism whereby elevated cAMP may interfere with neurite growth and regeneration.